How Public Private Partnerships Support Climate Mitigation and Adaptation Agenda in Cities - Alex Nduhura; MT Tshombe Lukamba; Thekiso molokwane; Stella Kyohairwe; Benedict Mugerwa; Innocent Nuwagaba; John Paul Settumba; Elvin Shava (International Journal of Supply Chain Management, 2022)
Climate change has become a major issue in cities that champion the path to the sustainable development of cities. Recent effort by COP 26 has buoyed the emphasis for improving neighborliness of climate and humankind. Since cities anchor national prosperity and act as and centre for policy making and actions for the country, they act as an important administrative structure for championing climate agenda. Although the literature on adaptation to climate change is rapidly expanding, little is known about how the adoption of new public management tool, public private partnerships(PPPs) contribute to climate sustainability, yet the adoption of PPPs is on the rise in traditional and emerging smart cities. Based on a review of literature, this study provides insights on how PPPs can enable city administrations to play a key role for supporting climate sustainable agenda of nations especially in Sub Saharan Africa that is considered a victim of climate change and yet this part of the world is deemed to have been insignificantly responsible for the climate change by largely affected negative effects of today’s climate change.